Selective counter design in quantum‐dot cellular automata nanotechnology. (21st December 2021) - Amirzadeh, Zaman; Gholami, Mohammad
Abstract: In this article novel counters based on quantum‐dot cellular automata (QCA) nanotechnology is designed. To have proper counter design, first new D flip‐flop with appropriate number of cells, area and delay is designed. Then, this flip‐flop is changed to have flip‐flop with set and reset abilities. Therefore, the proposed flip‐flop is used to design selective counters which can count for example from 0–5 or 2–5. However, in this article, compared to the best designs of the past works the number of cells, cross‐sectional area and delay are reduced by 3.57%, 18.18%, and 25% in counting 0–7 and the cell and cross‐sectional area are reduced by 46.88% and 52.17% in counting 0–5. In addition, in counter which can count from 0–7, the total and average energies are improved about 22.3% and 21.83% respectively. Also, for counters which counts from 0–5, the total and average energy dissipation has been improved about 53.01% and 53.08% respectively. It should be noted that the proposed selective counter in QCA technology which counts from 2 to 5 (both lower and upper values are different form 0 and 2 n −1) is firstly designed in this article. The proposed designs have few number of cells, small occupied area and low delay. Simulation results prove the theoretical anticipation.